If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + -14 = g Reorder the terms: -14 + 2g = g Solving -14 + 2g = g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. -14 + 2g + -1g = g + -1g Combine like terms: 2g + -1g = 1g -14 + 1g = g + -1g Combine like terms: g + -1g = 0 -14 + 1g = 0 Add '14' to each side of the equation. -14 + 14 + 1g = 0 + 14 Combine like terms: -14 + 14 = 0 0 + 1g = 0 + 14 1g = 0 + 14 Combine like terms: 0 + 14 = 14 1g = 14 Divide each side by '1'. g = 14 Simplifying g = 14
| 4(y+2)=15 | | ab-45=2a+4b+465.23+a | | 156/180=x/120 | | (1-2x)=32 | | 13x-68=-7x+12 | | (1/3*9)3 | | 3x+26/5=7 | | n+3n=180 | | 0.8(m+4)-0.3m= | | 5x=-6x-22 | | -6-j=4+j | | -27=-2x-7 | | -p-4=-12 | | -9-6x=-21 | | 8(2n-1)=6(6n+3)+8 | | 3/-4 | | 5p-16=10 | | -7x-12=2x-(5x-8) | | (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) |